A Dual-Position Loop LLADRC Control Method Based on Harmonic Gear Drive. (31st July 2022) - Cao, Yu; Wang, Fan; Li, Xin; Su, Xiuqin; Guo, Shan; Han, Junfeng; Xie, Meilin; Wang, Lei; Feng, Xubin
Abstract : High-resolution imaging has become a development trend and is widely used in military and civil fields. As the carrying equipment of imaging system, the speed stability of tracking turntable is the basis of high-resolution and stable imaging. At present, in the aerospace field, there are high requirements for peak power dissipation and holding torque, so flexible joints such as harmonic gear drive are mostly used to realize the function. The characteristics of flexible load have a great impact on the characteristics of motion control, which is easy to cause mechanical resonance, lead to system instability, and have a great impact on speed stability and position tracking accuracy. Therefore, it is necessary to study the servo system of flexible load. In order to solve the problems of high-precision position control and speed stability at low speed of flexible turntable with uncertain load, on the one hand, we comprehensively consider the advantages and disadvantages of semi-closed-loop and full closed-loop control and design a dual-position loop feedback control system combined with the analysis of dynamic equation to realize speed stability and high-precision position control. On the other hand, according to the requirements of the speed stability at low speed of the turntable, the tracking differentiator (TD) is designed innovatively through the language three-point interpolation subdivision and five-point pre-deduction calculation method. Finally, a dual-position loop LLADRC (language linear active disturbances rejection controller) control method based on harmonic gear drive is studied. By comparing the semi-closed loop, dual-position loop, dual-position loop LADRC (linear active disturbances rejection controller, ADRC), and dual-position loop LLADRC methods through simulation analysis, it can be shown that the double position LLADRC control method is obviously superior to other schemes in terms of rapidity, speed stability at low speed, and position tracking accuracy. The theoretical research is verified by experimental test. When the given speed is 0.1 ° / s, taking the pitch axis as an example, the pitch speed error is 0.0039 ° / s (3 σ ). When the maximum speed of the given curve is 20 ° / s and the maximum acceleration is 16 ° / s, the position tracking error is 0.0025° (3 σ ). This control method solves the problems of system instability and low-speed stability in high-precision control of turntable system based on harmonic gear drive and provides a method for high-precision control of high-resolution imaging turntable.